Critical remarks on the nomenclature of customs and fiscal control (Discourse of Law and Administration, 2023)
The article aims to demonstrate the accuracy of the thesis that the regulation of customsand fiscal control in the Act on National Revenue Administration is flawed from the point ofview of linguistic correctness and principles of lawmaking technique. Achieving this research goalrequires the use of primarily linguistic and grammatical interpretation, which is basic for the dogmaticmethod in legal sciences, to analyse the source material. The findings made in this way werealso confirmed by the conclusions drawn as a result of the method of legal semiotics. Names of legalterms should be created rationally and not cause information noise that hampers the legislator’scommunication with the addressee of the legislation. However, customs and fiscal control nomenclaturedo not meet this standard.
Keywords: customs and revenue control; nomenclature; National Revenue Administration